2019
DOI: 10.1155/2019/1349784
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-Binding Lectin Suppresses Peptidoglycan-Induced TLR2 Activation and Inflammatory Responses

Abstract: Peptidoglycan (PGN), as the major components of the bacterial cell wall, is known to cause excessive proinflammatory cytokine production. Toll-like receptor 2 (TLR2) is abundantly expressed on immune cells and has been shown to be involved in PGN-induced signaling. Although more and more evidences have indicated that PGN is recognized by TLR2, the role of TLR2 PGN recognition is controversial. Mannan-binding lectin (MBL), a plasma C-type lectin, plays a key role in innate immunity. More and more evidences show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…In the present study, we investigated the role of the p38 signaling pathway in RANKL-treated precursors in the presence of MBL protein, and have demonstrated that MBL has an inhibitory effect on osteoclast differentiation via downregulation of the p38/c-fos/NFATc1 signaling pathways. The result is consistent with several other observations showing that the regulation of monocytes activation and macrophage polarization by MBL under the inflammatory condition was associated with repression of p38 signaling pathway (45, 46).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we investigated the role of the p38 signaling pathway in RANKL-treated precursors in the presence of MBL protein, and have demonstrated that MBL has an inhibitory effect on osteoclast differentiation via downregulation of the p38/c-fos/NFATc1 signaling pathways. The result is consistent with several other observations showing that the regulation of monocytes activation and macrophage polarization by MBL under the inflammatory condition was associated with repression of p38 signaling pathway (45, 46).…”
Section: Discussionsupporting
confidence: 93%
“…The β-glucan on F. monophora cell wall can trigger the host lectin Dectin-1 on the surface of dendritic cells (DCs). Then Dectin-1 activates the transcription factor interferon regulatory factor 1 (IRF1), which is vital for IL-12A transcription, and consequently triggers T H 1 and T H 17 immune responses against the fungus [40,223,224]. However, in this process, the human mincle on the surface of DCs is simultaneously triggered by the pathogen via proper carbohydrate molecule(s).…”
Section: Host Lectinsmentioning
confidence: 99%
“…MBL also participates in the modulation of in ammation. A previous study reported that MBL could attenuate peptidoglycan induced in ammatory cytokine production and suppress nuclear translocation of NF-κBp65, phosphorylation of IκBα, MAPK p38, and ERK1/2 [33]. MBL may also inhibit autoreactive T cells' activation and proliferation via cell surface calreticulin in patients with silicosis [34].…”
Section: Mbl Alleviates Ecs Injury By Modulating Dcs Maturation and Pmentioning
confidence: 96%